2015
DOI: 10.1128/aem.02312-15
|View full text |Cite
|
Sign up to set email alerts
|

Involutin Is an Fe 3+ Reductant Secreted by the Ectomycorrhizal Fungus Paxillus involutus during Fenton-Based Decomposition of Organic Matter

Abstract: Ectomycorrhizal fungi play a key role in mobilizing nutrients embedded in recalcitrant organic matter complexes, thereby increasing nutrient accessibility to the host plant. Recent studies have shown that during the assimilation of nutrients, the ectomycorrhizal fungus Paxillus involutus decomposes organic matter using an oxidative mechanism involving Fenton chemistry (Fe2+ + H2O2 + H+ → Fe3+ + ˙OH + H2O), similar to that of brown rot wood-decaying fungi. In such fungi, secreted metabolites are one of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
1
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 45 publications
1
71
1
1
Order By: Relevance
“…In these fungi, Fenton chemistry reagents are generated by the secreted metabolites, including hydroquinones and catechols, that drive one‐electron reductions of Fe 3+ and O 2 (Hatakka and Hammel, ). The major Fe 3+ ‐reducing metabolite produced by P. involutus during Fenton‐based OM decomposition is the diarylcyclopentenone involution (Shah et al ., ); recent studies have shown that genes encoding enzymes involved in the biosynthesis of this metabolite are expressed during DOM decomposition (Shah et al ., ). Another group of fungal metabolites with aromatic and/or phenolic structures are the polyketides (Keller et al ., ; Hertweck, ).…”
Section: Discussionmentioning
confidence: 99%
“…In these fungi, Fenton chemistry reagents are generated by the secreted metabolites, including hydroquinones and catechols, that drive one‐electron reductions of Fe 3+ and O 2 (Hatakka and Hammel, ). The major Fe 3+ ‐reducing metabolite produced by P. involutus during Fenton‐based OM decomposition is the diarylcyclopentenone involution (Shah et al ., ); recent studies have shown that genes encoding enzymes involved in the biosynthesis of this metabolite are expressed during DOM decomposition (Shah et al ., ). Another group of fungal metabolites with aromatic and/or phenolic structures are the polyketides (Keller et al ., ; Hertweck, ).…”
Section: Discussionmentioning
confidence: 99%
“…In brown rot fungi, secreted metabolites are produced by the fungus that drive one‐electron reduction of Fe 3+ and O 2 , generating the Fenton chemistry reagents Fe 2+ and H 2 O 2 (Hatakka & Hammel, ). One such Fe 3+ ‐reducing metabolite, the diarylcyclopentenone involutin, is also secreted by P. involutus during SOM decomposition (Shah et al ., ), but the source of H 2 O 2 in P. involutus remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Two NRPS lacking the peptide-bond forming condensation domain have been biochemically characterized and shown to condense two aromatic α-keto acids to produce compounds with a quinone core as pigments or antimicrobials [63,65]. These secondary metabolites are also secreted as iron reductants to drive quinone redox cycling for lignin degradation [69]. Nevertheless, some intriguing PKS derived bioactive metabolites have been isolated from Basidiomycota.…”
Section: Biocatalysts Of Secondary Metabolismmentioning
confidence: 99%